Perbedaan Hasil Belajar Matematika Siswa Menggunakan Teori Bruner Dengan Teori Dienes Pada Kelas IV SD - Delvia, Fadilla; Ahmad, Syafri; Desyandri, Desyandri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
The research is aimed to find the difference of students learning outcomes of mathematics using Bruner theory with Dienes theory in students grade IV SDN Gugus 1 Kecamatan Sungai Puar. This research is quasi-experimental research with nonequivalent control group design. The sample was taken by using cluster sampling technique and the sample are students in class IV SDN 14 Simpang Ampek  which consists of two classes, 21 students in IV.A and 23 students in IV.B . The results of the calculation of the research data used are t-test obtained by tcount 2.6875 > ttable 2.0181 at the level of α 0.05. It can be concluded that there is a significant difference in student learning outcomes in square and rectangular material using Bruner's learning theory and Dienes’s learning theory in students grade IV SDN Gugus 1 Kecamatan Sungai Puar.